The Effect of Human Resource Digitalization on Employee Work Productivity: The Mediating Role of Digital Capability and the Moderating Role of Technological Adaptability - Andri Octavia; Riswan Riswan; Muhammad Oktaviannur (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Digitalization reshapes public sector human resource management practices. This study aims to examine the effect of human resource digitalization on employee work productivity, with digital capability as a mediating variable and technological adaptability as a moderating variable in a public sector organization. The research adopts a quantitative explanatory approach and was conducted at the Regional Revenue Agency (BAPENDA) of Pesawaran Regency. Data were collected from 77 employees using a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that human resource digitalization has a positive and significant effect on employee work productivity. Digital capability is found to significantly mediate the relationship between human resource digitalization and productivity, indicating that productivity improvements occur when employees possess adequate digital skills. Furthermore, technological adaptability strengthens the influence of human resource digitalization on work productivity, suggesting that employees’ adaptive capacity enhances the effectiveness of digital transformation initiatives. Overall, the findings highlight that digitalization alone is insufficient without the development of employee digital capability and adaptability. This study contributes to the literature by integrating the Resource-Based View and the Technology Acceptance Model to explain how and under what conditions digitalization improves employee productivity in public sector organizations.